Efecto de la herbivoría y coralivoría por peces en la supervivencia de corales trasplantados en el Caribe colombiano (2007)
Effect of herbivorous and corallivorous fishes on the survival of transplanted corals in the Colombian Caribbean. To examine the effects of herbivorous and corallivorous fishes on the survival of transplanted colonies of Montastraea annularis, Diploria labyrinthiformis and Porites astreoides, both transplanted and native colonies were full-cage enclosed and compared to open (uncaged) colonies, while caging effects were assessed with a partial-cage (roof treatment). To evaluate if transplant stress increased the corals availability to fish predation, comparisons of fish foraging intensity among transplanted versus native colonies were made. To determine the density of herbivorous and corallivorous fishes on the transplants area visual censuses were made. The transient herbivorous fishes (Scaridae and Acanthuridae) were the most abundant fishes, and the corallivorous fishes (mainly Chaetodontidae) were the scarcest. A negative effect of territorial herbivorous fishes on M. annularis transplants survival was observed, mainly early on the study. Fish foraging intensity was similar on transplanted and native colonies, but differed among coral species, being lowest on D. labyrinthiformis. Fast macroalgal growth inside full-cages due to reduced fish grazing was observed. This caused partial bleaching and partial mortality in some colonies, mainly of P. astreoides. No significant difference in healthy tissue percentages among full-cage and uncaged colonies on M. annularis and D. labyrinthiformis was found, while in P. astreoides there were evident differences. The results indicate a damselfish negative effect on transplants survival early on the study, which can change depending on the fish and coral species involved. Results also indicate a fish grazing positive effect, caused by the reduction of coral-algae competition pressure, mainly on P. astreoides. Parrotfishes seem to affect corals survival both negatively through direct biting, and positively by controlling algal growth. Overall, coral transplant success was almost unaffected by fish foraging activity although several differences among coral species were obvious in relation to colony shape. Additionally, the interaction among herbivorous fish grazing and coral-algae competition balance appear important in determining transplant survival. Rev. Biol. Trop. 55 (3-4): 825-837. Epub 2007 December, 28.